KARAKTERISTIK LATEKS BEBERAPA KLON KARETIRR SERI 200 DIPENGUJIAN PLOT PROMOSI - Sayurandi Sayurandi (Jurnal Agro Estate, 2017)
The rubber breeding and selection activities in Indonesia aimed to produce superior rubber clones, growth vigorous, good secondary characteristics, and good latex quality. The objective of the research was to know the latex quality characteristic ofsome rubber clones ofIRR 200 series in Plot Promotion Trial. The research were done at Sungei Putih Experimental Garden and Rubber Technology Laboratory on September - November 2015. Exactly 4 rubber clones ofIRR 200 series used in this research, namely clone IRR 208, IRR 210, IRR 211, and IRR 220. The research result showed that clone IRR 208, IRR 210, IRR 211, and IRR 220 had concentrated latex with dry rubber content between 57.7—59.5% and amount solid content between 59.4 - 60.9%. Based on the timing of mechanical stability showed that clone IRR 210, IRR 211, and IRR 220 had rapid responses, while clone IRR 208 had moderate response to the addition ofammonium laurate. Those clones could be turned into concentrated latex as raw materialfor making latexfinishedgoods which worth high quality.